KONSEP KESESUAIAN SISTEM ANGGARAN DAN AKUNTANSI KEUANGAN DALAM SISTEM AKUNTANSI UNIVERSITAS - Mujilan, Agustinus (Widya Warta, 2015)
This study aims to design a university accounting system based on budget and financial accounting reporting. It focuses on the explanation of the basic handling of accounting systemin higher learning institutes which can accommodate the budget system for financial accounting reporting of non-profit organization. Basically, this research identifies therequirement of system which suits the software generally used to handle accounting processes, such as Excel and Mysql web based. The method applied is the part of SystemDevelopment Life Cycle (SDLC), especially the analysis and design system. The results revealed the concept of accounting coding, budgeting coding, and unit coding to support theautomation system, as well as the database structure, accounting transaction processing and the form of accounting data recording. The process started with the designing of database and table structure, journal, general ledger, financial accounting reporting, and budget reporting. So, this study explained the process of transaction handling to achieve the output of budget and financial accounting reporting.